The Influence Of Green Beansâs Flesh Extract (Phaseolus vulgaris L.) On Total Cholesterol Blood Level Of White Rat (Rattus norvegicus) Hypercholesterolemia Models - Shaufika, Yunindra Ken; Aisyah, Siti; Hermawan, Danus (Nexus Kedokteran Translasional, 2016)
Introduction: Coronary heart disease is often suffered by Indonesiaan which are characterized by excessive cholesterol levels. Beans is a leguminous plant that is widely consumed by Indonesian. Beans have compounds that can lower cholesterol levels in the fruit are flavonoids, saponins and polyphenols. Flavonoids work by inhibiting the action of enzymes that cholesterol forming HMG CoA reductase inhibitor. Saponins inhibit cholesterol absorption in the intestine. Polyphenols work in inhibiting the oxidation of cholesterol. Statins currently used as a causative therapy in cases of hypercholesterolemia. However, use of these drugs gives the adverse side effects of the body. Therefore, researchers wanted to find out more about the influence of the content of the fruit flesh snaps against total blood cholesterol levels. Methods: ThisÂ  research is as experimental laboratoric research with Randomized Controlled Trial design that post-test only control group design, have done in Histology Laboratorium of the University of March Surakarta. The subjectÂ  are 25 male whiteÂ  rats, Wistar strain, aged 3 months, weighing 200 Â± 10 gram grams. Green beansâs flesh made by using maceration method. The rats were divided randomly into 5 groups, each group consisting of 5 rats. In the negative control group was only given regular feed and distilled water, the positive control group was given hiperkolesterolemic feed, PTU and distilled water. Whereas in the treatment group was given hiperkolesterolemic feed, PTU and water as well as 50 mg of extract of the green beansâs flesh in treatment group I, 100 mg extract of the green beansâs flesh in the treatment group II and 150 mg extract of the green beansâs flesh in the treatment group III. All rats total blood cholesterol levels checked after the treatment period of 35 days. The data were analyzed by one-way ANOVA with SPSS for Windows version 22. Results: The result ofÂ  one-way ANOVA test showed no significant total cholesterol blood levek difference between 5 groups of rats with p=0,299. Conclusions: The conclusion of the researchÂ  is there is no effect between green beans extract on total cholesterol blood levels of white rat. Researcher suggests to do similar researchs with better method. Keywords: Green beansâs flesh extract, total cholesterol, white rat, hypercholesterolemia